Reduced Efficacy of Insecticide-treated Nets and Indoor Residual Spraying for Malaria Control in Pyrethroid Resistance Area, Benin - N’Guessan, Raphael (Centers for Disease Control and Prevention, 2007)
The pyrethroid knockdown resistance gene (kdr) has become widespread in Anopheles gambiae in West Africa. A trial to test the continuing efficacy of insecticide-treated nets (ITN) and indoor residual spraying (IRS) was undertaken in experimental huts at 2 sites in Benin, 1 where kdr is present at high frequency (Ladji), the other where An. gambiae is susceptible (Malanville). Holes were made in the nets to mimic worn nets. At Malanville, 96% of susceptible An. gambiae were inhibited from blood-feeding, whereas at Ladji feeding was uninhibited by ITNs. The mortality rate of An. gambiae in ITN huts was 98% in Malanville but only 30% at Ladji. The efficacy of IRS was equally compromised. Mosquitoes at Ladji had higher oxidase and esterase activity than a laboratory-susceptible strain, but this fact did not seem to contribute to resistance. Pyrethroid resistance in An. gambiae appears to threaten the future of ITN and IRS in Benin.